Induction of pigment production through media composition, abiotic and biotic factors in two filamentous fungi (2019)
ABSTRACT: In addition to plant-derived, fungal pigments have become an alternative in respect to synthetic ones. Besides Monascus sp., several pigment-producing fungi do not have culture conditions well-established yet. In this research, media composition, light wavelength and co-culture were evaluated, results were reported in Absorbance Units per gram of biomass (AU/Bgr). For Fusarium oxysporum a C:N ratio above 7 was advantageous, using both complex and defined media; blue LED light increased the AU/Bgr value from 18013 to 344; co-culture did not enhance pigment production. In Aspergillus chevalieri a high C:N ratio with glucose as carbon source was ideal. When exposing cultures to light, UV and red light gave the highest pigmentation; moreover, differential UV-VIS spectra in all wavelengths suggested production of additional pigments. Particularly a pigment observed when cultured in green light was also found in co- culture with yeast and there was an improvement of AU/Bgr value of 52549%. This is the first report regarding light effect and co-culture for these fungi, as well as C:N ratio for A. chevalieri.